Nutrition and oral status in elderly people - Mitsuyoshi Yoshida; Ryo Suzuki; Takeshi Kikutani (Elsevier, 2014)
This study reviewed the relationship between oral status and nutritional disorders such as obesity and sarcopenia. A literature search was performed using PubMed to find articles published in and after 2000 by using the following search terms: elderly, nutrition, tooth, tooth loss, mastication, and oral function. Although the literature search revealed that further well-designed studies are difficult controlling all confounding factors thought to influence nutritional status, it may be concluded that tooth loss leads to decreased vegetable and fruit intake and results in nutritional disturbance. This was especially prominent in elderly people who required nursing care. Moreover, although it is becoming clear that not wearing dentures increases the risk of undernutrition, the effect of denture therapy remains debatable. Elderly people in need of nursing care should be studied in future investigations on the relationship between nutrition and oral status because this population is at risk of malnutrition considering both functional and structural problems.